Farinhadas na zona rural de Teresina-PI: valorização da identidade cultural alimentar indígena - Gonçalves, Marina Miranda Ribeiro (2024)
Eating is part of the life of human beings. In addition to its biological function, it helps to build the cultural identity of individuals, as they relate to each other socioculturally through food. Furthermore, food belongs to a symbolic system, which through culture defines some habits to the detriment of others. If we review the eating practices of indigenous peoples, we will find a vast culinary contribution, including the use of cassava and its derivatives. Cassava (Manihot esculenta Crantz) is one of the most popular food products in Brazil even before colonization. Farinhada is the dismantling of cassava, that is, it is a popular event where the entire process of transforming this root into food takes place. Farinhada goes beyond learning methods, it is first and foremost a space in which individuals, members of the same community or family, learn to relate to each other and to the world. The farinhada preserves the traditional indigenous knowledge, as the artifacts used, the knowledge and the ways of making carried out and taught in the farinhada carry symbols of the food identity of these people. In this sense, the village of Boqueirão, in the Eastern Rural Zone of Teresina-PI, maintains the tradition of farinhada, helping to preserve the material and immaterial goods inherent to this custom. However, the transformations resulting from globalization and industrialization affect the tradition of the farinhada. Thus, the present study aimed to research the farinhada that take place in the community flour house of the village of Boqueirão, located in the East Rural Zone of Teresina/PI, in order to value the ancestral indigenous food cultural identity. The study is characterized as qualitative. As for the proposed objectives, the research is descriptive and exploratory. Bibliographic and field research data were collected from September 2021 to December 2023. In relation to technical procedures, the work can be defined as bibliographic, documentary and field. The ethnographic method was used in field research. Thus, through narrative and semi-structured interviews, 10 people who actively participate in the farinhada were interviewed. The results of the study revealed that in the village of Boqueirão, the tradition of farinhada is maintained, but it has been modified, since the globalization and industrialization of food homogenize the palates worldwide, as well as the younger residents of the community work in the city in often precarious functions. Unfortunately, there is a great risk of losing the farinhada in the next generations of the Boqueirão village. It is essential to carry out further studies that promote the appreciation of this tradition, which is so important for the state of Piauí and for Brazil.